2016
DOI: 10.3109/09638288.2016.1152603
|View full text |Cite
|
Sign up to set email alerts
|

Balance impairment limits ability to increase walking speed in individuals with chronic stroke

Abstract: Purpose Determine the relationship between balance impairments and the ability to increase walking speed (WS) on demand in individuals with chronic stroke. Methods WS and Berg Balance Scale (BBS) data were collected on 124 individuals with chronic stroke (>6 months). The ability to increase WS on demand (walking speed reserve, WSR) was quantified as the difference between participants’ self-selected (SSWS) and maximal (MWS) walking speeds. Correlation, regression and receiver operating characteristic (ROC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 34 publications
3
58
1
Order By: Relevance
“…Consistent with the finding of the present study, other studies have also indicated that balance control (based on the BBS) is related to ambulatory function and has the ability to predict walking performance 4 , 16 , 17 , 18 , 19 , 20 ) . Although they have used different measuring tools for evaluating walking performance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the finding of the present study, other studies have also indicated that balance control (based on the BBS) is related to ambulatory function and has the ability to predict walking performance 4 , 16 , 17 , 18 , 19 , 20 ) . Although they have used different measuring tools for evaluating walking performance.…”
Section: Discussionsupporting
confidence: 93%
“…A majority of the gait cycle is spent in single leg stance and during this phase, the center of mass is traveled outside the margin of stability, thus making this phase inherently unstable, Therefore, balance recovery is critical to having a stable and safe ambulation. Following stroke, not only ambulation capacity is limited, but also due to weakness, spasticity and changes in muscle activation pattern, balance control is reduced 15 , 16 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This might be of relevance for clinicians as walking speeds and balance are well associated. 4,5 For example, if a patient achieves a score of 19 and greater on the Mini-BESTest but does not have walking speeds greater than 0.8 m/s, then this may indicate that individuals with stroke maybe slowing down their walking due to an underlying problem other than balance, such as strength deficits, fear of falling or cognitive processing. The clinician could use this information to target appropriate treatment activities to achieve faster walking speeds.…”
Section: Discussionmentioning
confidence: 99%
“…Given this variation in functional recovery, it is likely that a single MDC may be inappropriate for all individuals. In particular, slower walkers tend to have less gait speed reserve, 19 and thus may vary their gait speed less on a day to day basis. As a result, a slower walker may not need as large a change in gait speed as a faster walker to constitute a 'real' change.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that individuals with slower gait speeds would have smaller MDCs, due to the limited ability to vary gait speed compared to individuals with faster gait speeds. 19 It is important to present MDC's for a range of gait speeds, including the thresholds based on walking performance, 23 to inform future work.…”
Section: Introductionmentioning
confidence: 99%